Land cover classification using satellite optical and radar image fusion - Liu, Yunwei (2019)
Synthetic Aperture Radar (SAR) is an advanced radar imaging technology that is able to produce high-resolution imagery of the Earth's surface in all weather. Other systems such as optical camera could also provide high-resolution land mapping images, but they could be affected by adverse weather conditions, like clouds and haze. Compared to optical images, SAR images usually have lower resolution but better land type features. This project is to conduct an image fusion study to combine the good features of SAR images and optical images to produce a better imagery result with both land classification effects from SAR images and earth surface details from optical images.